Implementation of Madrasah Exams Using UMBKS Application Offline in the Religious Field for Grade IX Students at MTs Nurul Ilmi Karondang - Herman; Muh. Dahlan; Muh. Akib D; Usman; Firman (Universitas Muhammadiyah Palu, 2024)
This thesis discusses the implementation of madrasah exams using the UMBKS application offline in the religious field for grade IX students at MTs Nurul Ilmi Karondang. This is based on the geographical location of MTs Nurul Ilmi, which lacks internet network coverage, preventing the implementation of online madrasah exams. Therefore, the use of the UMBKS application offline becomes an alternative solution for this madrasah. The objectives of this research are (1) to describe the implementation of madrasah exams using the UMBKS application offline, (2) to examine and analyze the supporting and inhibiting factors in the implementation of madrasah exams using the UMBKS application offline in the religious field, and (3) to describe the utilization of computer network offline in conducting madrasah exams using the UMBKS application in the religious field for grade IX students at MTs Nurul Ilmi Karondang. This research employs a qualitative approach oriented towards phenomenology, with research subjects including the madrasah head, operator, and teachers involved in the implementation of madrasah exams. Data collection techniques include observation, interviews, and documentation. The data analysis technique follows the interactive model by Miles and Huberman, involving four stages: data collection, data condensation, data display, and data verification. The validity of the research data is ensured through triangulation. The results of this research are as follows: (1) the implementation of madrasah exams using the UMBKS application offline in the religious field at MTs Nurul Ilmi Karondang can be considered successful. The implementation involves several stages, including planning through teacher orientation and student simulation, infrastructure verification by preparing supportive equipment, schedule determination, and the actual implementation of madrasah exams using the UMBKS application offline. (2) There are several supporting and inhibiting factors in the implementation of madrasah exams using the UMBKS application offline, such as government support from the Ministry of Religious Affairs in Mamuju Tengah District for madrasahs in remote areas without internet coverage, limited operational costs for conducting madrasah exams, parents' role and economic factors affecting their response to madrasah exams, and the use of various smartphones by students causing disruptions during the offline implementation of the UMBKS application. (3) The utilization of computer network offline is not fully maximized during the implementation of madrasah exams due to a lack of understanding and proficiency in IT among some teachers.